Analysis of The Quality of The Eskanusa.Com Website on User Satisfaction with the Webqual 4.0 Method - Mochammad Lazzuardi Effendi; Nurajijah Nurajijah; Siti Nurlela (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2021)
Information technology is currently growing rapidly, one of which is the use of the internet. PT. Eskanusa Putraco is one of the companies that use the internet as a medium to sell goods online on their website, namely eskanusa.com. User satisfaction with the use of the website will affect employee performance. This study aims to analyze how satisfied users are in their activities on the escanusa.com website using the webqual 4.0 method with 3 independent variables, namely Usability, Information Quality, Interaction Quality, Service (Service Interaction Quality), and 1 dependent variable, namely Overall (Overall Impression) / User Satisfaction. Data collection techniques used questionnaires that were distributed to 44 respondents. Data management is carried out using descriptive statistics to calculate the overall data obtained, which is then tested for validity and reliability tests to find out the data obtained are valid and reliable, followed by classical assumption tests using 3 tests, namely normality, multicollinearity, and heteroscedasticity to determine if symptoms occur. or not on the data, and multiple linear regression analysis to determine the independent variable has an influence with the dependent variable with the F test and T test. It is known that the variables (usability), information quality (information quality), interaction quality, service (service interaction quality) affect user satisfaction, the results obtained are 40% or not good enough because the variables of information quality and interaction quality, which are known to have not good enough influence on users.